18F-Fluoride and 18F-Fluorodeoxyglucose Positron Emission Tomography After Transient Ischemic Attack or Minor Ischemic Stroke: Case–Control Study. (March 2017) - Vesey, Alex T.; Jenkins, William S. A.; Irkle, Agnese; Moss, Alastair; Sng, Greg; Forsythe, Rachael O.; Clark, Tim; Roberts, Gemma; Fletcher, Alison; Lucatelli, Christophe; Rudd, James H. F.; Davenport, Anthony P.; et al.
Abstract : Background—: Combined positron emission tomography (PET) and computed tomography (CT) can assess both anatomy and biology of carotid atherosclerosis. We sought to assess whether 18 F-fluoride or 18 F-fluorodeoxyglucose can identify culprit and high-risk carotid plaque. Methods and Results—: We performed 18 F-fluoride and 18 F-fluorodeoxyglucose PET/CT in 26 patients after recent transient ischemic attack or minor ischemic stroke: 18 patients with culprit carotid stenosis awaiting carotid endarterectomy and 8 controls without culprit carotid atheroma. We compared standardized uptake values in the clinically adjudicated culprit to the contralateral asymptomatic artery, and assessed the relationship between radiotracer uptake and plaque phenotype or predicted cardiovascular risk (ASSIGN score [Assessing Cardiovascular Risk Using SIGN Guidelines to Assign Preventive Treatment]). We also performed micro PET/CT and histological analysis of excised plaque. On histological and micro PET/CT analysis, 18 F-fluoride selectively highlighted microcalcification. Carotid 18 F-fluoride uptake was increased in clinically adjudicated culprit plaques compared with asymptomatic contralateral plaques (log10 standardized uptake valuemean 0.29±0.10 versus 0.23±0.11, P =0.001) and compared with control patients (log10 standardized uptake valuemean 0.29±0.10 versus 0.12±0.11, P =0.001). 18 F-Fluoride uptake correlated with high-risk plaque features (remodeling index [ r =0.53, P =0.003], plaque burden [ r =0.51, P =0.004]), and predicted cardiovascular risk [ r =0.65, P =0.002]). Carotid 18 F-fluorodeoxyglucose uptake appeared to be increased in 7 of 16 culprit plaques, but no overall differences in uptake were observed in culprit versus contralateral plaques or control patients. However, 18 F-fluorodeoxyglucose did correlate with predicted cardiovascular risk ( r =0.53, P =0.019), but not with plaque phenotype. Conclusions—: 18 F-Fluoride PET/CT highlights culprit and phenotypically high-risk carotid plaque. This has the potential to improve risk stratification and selection of patients who may benefit from intervention. Abstract : Supplemental Digital Content is available in the text.